Los artesanos del mueble en Barcelona a finales de siglo XVIII: el espacio doméstico - Mónica Piera Miquel (Nuevo mundo - Mundos Nuevos, 2008)
This work focuses on the homes of the craftsmen who constructed the furniture that decorated the houses in Barcelona at the end of the eighteenth century. We want to know how they lived, what was their standard of life, in what conditions they worked and what was their familiar background. We have analyzed a total of 20 post-mortem inventories of cabinet-makers, from 1780 to 1784 and from 1790 to 1794, stored at the Archivo Histórico de Protocolos de Barcelona (AHPB). We have also looked for other documents that made reference to those craftsmen in order to obtain a wider perspective of their life. The documents reveal a considerable difference in the quality of their lives: While some of them lived in very small houses and without any comfort, few, a small group achieved a quality of life similar to the lower bourgeoisie. When the economic level allowed it, the craftsmen follow the tendencies of the superior economic groups of the society. We observed a greater specialization in the house and the objects that conform it, a greater quality of materials and the inclusion of objects and furniture of fashion.